Effectiveness and Implementation of a Text Messaging mHealth Intervention to Prevent Childhood Obesity in Mexico in the COVID-19 Context: Mixed Methods Study - Ana Lilia Lozada-Tequeanes; Florence L Théodore; Edith Kim-Herrera; Armando García-Guerra; Amado D Quezada-Sánchez; Rocio Alvarado-Casas; Anabelle Bonvecchio (JMIR Publications, 2024)
BackgroundPromoting physical activity (PA) and healthy feeding (HF) is crucial to address the alarming increase in obesity rates in developing countries. Leveraging mobile phones for behavior change communication to encourage infant PA and promote HF is particularly significant within the Mexican context. ObjectiveThis study aims to explore the effectiveness and feasibility of mHealth interventions aimed at promoting PA and HF among primary caregivers (PCs) of Mexican children under the age of 5 years. Additionally, the study aims to disseminate insights gained from intervention implementation amidst the COVID-19 pandemic and assess the potential of behavior change mHealth interventions on a broader population scale. MethodsNUTRES, an mHealth intervention, underwent an effectiveness-implementation hybrid trial. Over 36 weeks, participants in the intervention group (IG), totaling 230 individuals, received approximately 108 SMS text messages tailored to their children's age. These messages covered topics such as PA and HF and emphasized the significance of proper child nutrition amidst the COVID-19 pandemic. NUTRES participants were recruited from both urban and rural health units across 2 states in Mexico. Given the COVID-19 context, both baseline and follow-up surveys were conducted via mobile or fixed telephone. The evaluation of effectiveness and implementation used a mixed methods approach. Qualitative analysis delved into participants' experiences with NUTRES and various implementation indicators, including acceptance, relevance, and coverage. Grounded theory was used for coding and analysis. Furthermore, difference-in-differences regression models were used to discern disparities between groups (comparison group [CG] versus IG) concerning knowledge and practices pertaining to infant PA and HF. ResultsOf the total 494 PCs enrolled in NUTRES, 334 persisted until the end of the study, accounting for 67.6% (334/494) participation across both groups. A majority of PCs (43/141, 30.5%, always; and 97/141, 68.8%, sometimes) used the SMS text message information. Satisfaction and acceptability toward NUTRES were notably high, reaching 98% (96/98), with respondents expressing that NUTRES was "good," "useful," and "helpful" for enhancing child nutrition. Significant differences after the intervention were observed in PA knowledge, with social interaction favored (CG: 8/135, 5.9% vs IG: 20/137, 14.6%; P=.048), as well as in HF practice knowledge. Notably, sweetened beverage consumption, associated with the development of chronic diseases, showed divergence (CG: 92/157, 58.6% vs IG: 110/145, 75.9%; P=.003). In the difference-in-differences model, a notable increase of 0.03 in knowledge regarding the benefits of PA was observed (CG: mean 0.13, SD 0.10 vs IG: mean 0.16, SD 0.11; P=.02). PCs expressed feeling accompanied and supported, particularly amidst the disruption of routine health care services during the COVID-19 pandemic. ConclusionsWhile NUTRES exhibited a restricted impact on targeted knowledge and behaviors, the SMS text messages functioned effectively as both a reminder and a source of new knowledge for PCs of Mexican children under 5 years of age. The key lessons learned were as follows: mHealth intervention strategies can effectively maintain communication with individuals during emergencies, such as the COVID-19 pandemic; methodological and implementation barriers can constrain the effectiveness of mHealth interventions; and using mixed methods approaches ensures the complementary nature of results. The findings contribute valuable evidence regarding the opportunities and constraints associated with using mobile phones to enhance knowledge and practices concerning PA and HF among PCs of children under 5 years old. Trial RegistrationClinicalTrials.gov NCT04250896; https://clinicaltrials.gov/ct2/show/NCT04250896